PENGARUH UKURAN DEWAN DIREKSI, KOMISARIS INDEPENDEN, KERAGAMAN GENDER, DAN KOMPENSASI EKSEKUTIF TERHADAP PENGHINDARAN PAJAK PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia 2017-2019) - Bill Hudha; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2021)
This study aims to obtain empirical evidence on the effect of board size, proportion of independent commissioners, gender diversity and executive compensation on tax avoidance. Corporate tax avoidance is measured using the effective tax rate (ETR). This study uses quantitative research methods using multiple linear regression analysis. The population of this study is all companies engaged in the manufacturing sector listed on the Indonesia Stock Exchange from 2017 to 2020. The sample was selected using a purposive sampling method and obtained 117 companies.         The results of the test show that gender diversity has a significant effect on tax avoidance, while board of directors size, the proportion of independent commissioners and executive compensation do not have a significant effect on tax avoidance.